Differentiated Threat and the Genesis of Prejudice: Group-Specific Antecedents of Homonegativity, Islamophobia, Anti-Semitism, and Anti-Immigrant Attitudes. (13th February 2018) - Meuleman, Bart; Abts, Koen; Slootmaeckers, Koen; Meeusen, Cecil
Abstract: In this article, we argue that an exclusive focus on the generalized aspect of prejudice limits understanding of the structure and genesis of prejudice towards particular outgroups. In order to conceptualize the specific nature of particular prejudices, we propose the differentiated threat approach. This framework postulates that different outgroups challenge diverse realistic and symbolic interests, and that these outgroup specific threats affect various socioeconomic strata and cultural groups differentially. The differentiated threat approach is applied to analyse majority-group Belgians' attitudes towards immigrants, Muslims, Jews, and homosexuals. The results show that a common denominator of prejudice can be distinguished, but that the prejudices towards the various outgroups contain substantively relevant unique components that are influenced by socio-demographic and attitudinal predictors in diverging ways. Gender traditionalism is found to reinforce Homonegativity and temper Islamophobia at the same time. Feelings of relative deprivation are more strongly related to Islamophobia than to other forms of prejudice, and are unrelated to homonegativity. Religious involvement plays a more decisive role in the formation of anti-Semitism and Homonegativity than it does in the other forms of prejudice. Anti-immigration attitudes show a class gradient that is absent in attitudes towards other outgroups. Our results evidence that the concrete realization of attitudes towards a specific outgroup cannot be understood without paying attention to structural and contextual factors, such as social positions, the nature of intergroup relations, power balances, and elite discourses.